Comparative metagenomic analysis of human intervertebral disc nucleus pulposus and cartilaginous end plates - Shanmuganathan, Rajasekaran; Tangavel, Chitraa; K S, Sri Vijay Anand; Muthurajan, Raveendran; Nayagam, Sharon Miracle; Matchado, Monica Steffi; Rajendran, Sunmathi; Kanna, Rishi Mugesh; Shetty, Ajoy Prasad (Frontiers in Cardiovascular Medicine, 2022)
Study design The diversity of microflora inhabiting endplate (EP) and nucleus pulposus (NP) tissues of human intervertebral disc (IVD) was profiled through NGS-supported 16S rRNA amplicon sequencing. Sixteen EP and their corresponding NP were excised from the brain-dead voluntary organ donors with no clinical history of low back pain, and 12 herniated and 8 degenerated NP tissues isolated from the patients undergoing spinal surgery were subjected to study the alteration in the microbial diversity. Objective(s) To understand in normal IVD, whether the colonization of bacteria to the NP is through the EP in discs with intact annulus fibrosus. To identify significantly differing microbial population(s) between normal and diseased IVD (NP). Background of the study There is increasing evidence for subclinical infection by fastidious low, growing bacteria to be a cause of disc degeneration. Although the presence of bacteria in NP has been reported well in literature, the source of bacteria is not clearly proved as the disc is avascular in healthy condition. Documentation of similar bacterial populations in the EP and NP may add proof that bacterial inoculation of NP occurs via the EP. Materials and methods Sixteen EP and their corresponding NP excised from brain-dead voluntary organ donors with no history of back pain and 20 diseased discs collected from patients undergoing microdiscectomy/fusion surgery were used for profiling microbiome through 16S rRNA amplicon sequencing using primers specific for V1-V9 hypervariable regions. Changes in bacterial diversity and abundance were analysed to identify the key microbial populations in normal IVD NP and EP tissues and those significantly altered in diseased IVD (NP). Results NP and EP shared a similar spectrum of microbiome but with varying abundance. The five dominant phyla identified were Proteobacteria, Firmicutes, Actinobacteria, OD1, and Bacteroidetes. Proteobacteria was found to be the most abundant phyla in both NP (62%) and EP (53%) of the normal IVD. This was followed by Firmicutes (16%), Actinobacteriota (11%), OD1 (Parcubacteria) (7.6%), and Bacteroidetes (2%) in NP and Firmicutes (23.4%), OD1 (Parcubacteria) (17.6%), Actinobacteriota (2.8%), and Bacteroidetes (2.6%) in EP, respectively. Under diseased conditions, Proteobacteria (68%) was dominant when compared with other phyla. However, there was no significant difference in the abundance of Proteobacteria between the normal and diseased discs. Interestingly, the other dominant phyla such as Firmicutes (Normal-NP: 16.2%; Diseased-NP: 4.02%) and Actinobacteria (Normal-NP: 11%; Diseased-NP: 0.99%) showed a significant reduction in degenerated discs. To understand the key microbial populations that are significantly altered during disease, correlation analysis was performed among the three phyla, which revealed a negative correlation in the ratio of Actinobacteria + Firmicutes vs. Proteobacteria (p = 0.001) in DD. Conclusion Results of our study clearly demonstrated a similar bacterial diversity but with varying abundance between the EP and NP, suggesting the existence of the endplate–nucleus pulposus axis in the normal IVD microbiome. Further, our results have indicated that the changes in the abundance of Actinobacteria + Firmicutes vs. Proteobacteria during DDD need further investigation.